Implementation of Traditional Games as Unplugged Activities to Foster Computational Thinking in Early Childhood Education - Khoe Yao Tung (Aletheia Christian Educators Journal, 2025)
This study investigates the integration of traditional Indonesian social games engklek (hopscotch) and congklak (mancala)—as culturally embedded, unplugged activities aimed at fostering computational thinking (CT) in early childhood education (PAUD). Utilizing a classroom-based action research methodology, the intervention spanned four weeks, involving 15 children in the experimental group and 16 in the control group. Each week featured structured, developmentally appropriate gameplay sessions designed to target key CT dimensions: decomposition, pattern recognition, abstraction, and algorithmic thinking. Quantitative analysis, using the Mann–Whitney U test, revealed statistically significant differences in CT competencies between the two groups, demonstrating the intervention’s effectiveness. Additionally, the Wilcoxon test was employed to compare the effects of the games on boys and girls in the experimental group. Complementing the quantitative findings, qualitative analysis of systematically analysed observational field notes and classroom documentation revealed recurring patterns related to children’s cognitive engagement and CT development. The results emphasize the pedagogical potential of traditional games as culturally responsive and contextually meaningful tools for cultivating foundational cognitive skills in young learners. This research further highlights the essential role of culturally grounded, play-based learning strategies in enhancing both cognitive and motoric fluency, underscoring the importance of contextually relevant early childhood educational practices.